Digital business, work and consumption in a service relation: a case study of a delivery platform company - Cruz, Sofia Alexandra; Sales Oliveira, Catarina (Frontiers in Sociology, 2025)
The platform economy has contributed to new ways of organising business, work, and consumption. To understand the shape and scope of these changes, it is crucial to pay simultaneous attention to these three domains. The new ways of organising, dividing and coordinating work are interlinked with specific ways of consuming services made available by digital platforms. This article analyses a case study of a delivery platform company with a specific business model marked by strong territorial roots and promoting relational proximity between the platform, workers, and clients. It proposes an approach to the service relation between the platform, workers, and clients allowing to explore institutional, intersubjective and spatial–temporal dimensions that shape it. Intersubjective, because they point to particular modes of communication and involvement between the parties. Institutional, as the platform reflects the organisational environments within which it operates. Spatio-temporal, as this service relation promotes flexible spatial and temporal arrangement that articulates various urban actors.